GENETIC POTENTIAL OF AFRO-ASIAN AND INDO-CHINESE COTTON SPECIES - Khasan Muminov (Modern American Journals, 2025)
The article presents the results of the studies to identify genetic and breeding posibilities with use the comparative morphology methods, intra and interspecific hybridization, practical genetics. The studies revealed morphological characteristics and economic-valuable traits of the wild, ruderal and cultural-tropical forms of G.herbaceum L., G.arboreum L. and also new intra- and interspecific hybrids. The degree of compatibility of the intraspecific forms, their specific features with intra- and interspecific hybridization was determined. The features of inheritance and the degree of heritability of some morphological and economically valuable traits in the intra- and interspecific hybrids F1 and F2.